Carrier Based Pulse Width Modulation Control of a Non-Square Direct Matrix Converter with Seven-phase Input and Three-phase Output - Sk Moin Ahmed; Haitham Abu-Rub; Zainal Salam (Institute of Advanced Engineering and Science, 2013)
This paper presents pulse width modulation technique for a direct ac-ac converter. The converter has seven-phase input supply and three-phase output. The input supply may be obtained from a seven-phase wind energy generation system with variable output voltage magnitude and frequency. The output of the proposed converter topology may be fed to the three-phase stiff grid system. Thus the requirement of the modulation of the ac-ac converter is to produce fixed voltage and fixed frequency output while the input can be variable. Additionally the output voltage gain should be high. Simple carrier-based PWM technique is suggested and harmonic injection scheme is proposed to enhance the output voltage magnitude. The output voltage reaches 90% of the input supply voltage with the proposed technique. An additional control block is used to stabilize the output voltage and frequency of the converter. Simulation results are shown in the paper for the verification of the proposed scheme.DOI: http://dx.doi.org/10.11591/ijpeds.v3i3.4315